Assessment of Supply Chain Integration in Ethiopian Textile Industries - Gamachu, Girma Abdissa; Patrick, Dr. Harold Andrew (The journal of contemporary issues in business and government, 2022)
The study develops and implements an integrated supply chain performance measurement framework that provides a more thorough approach to investigating supply chain performance measurement by merging supply network macro operations and decision-making levels. The conceptual model framework is built on performance and supply chain related theories. The study investigates the performance of supply chain integration along with the performance indicators in the textile industries in Ethiopia. The quantitative research was used to measure financial measurement indicators, Quality, time measurement indicators, productivity indicator measurement, internal supply chain integration, external or customer integration and information communication technology indicators. The data was treated using SPSS version 20. The data was collected from textile industry professionals through self-reported method and the common method bias analysis was done. The survey was administered/mailed to eighteen hundred (800) textile industry professionals and only (385) three hundred and eighty-five were able to complete the study questionnaire. Eight standardized, valid, and reliable questionnaires were adopted to collect primary data from the employees of top textile manufacturing Organizations’ located in Addis Ababa - Ethiopia. It was found that supply chain integration performance is influenced by the indicators such as financial measures, time, quality, productivity, internal supply chain, and external supply chain and information communication technology. Multiple regression analysis for the hypotheses indicated that: Performance sub-dimensions i.e., financial measures, time, quality, productivity, internal supply chain, and external supply chain and information communication technology significantly predicted supply chain integration performance in Textile industry.